An assessment of achievements of the WEEE Directive in promoting movement up the waste hierarchy: experiences in the UK. (15th March 2019) - Cole, Christine; Gnanapragasam, Alex; Cooper, Tim; Singh, Jagdeep
Highlights: Explores barriers to applying the waste hierarchy for e-waste. 30 semi-structured expert interviews examined the impact of the WEEE Directive. Legislation has prompted innovation in recycling and higher capture rates. Recovery through recycling is limited to easily salvageable materials. Waste prevention and reuse of EEE is often neglected in favour of recycling. Abstract: Rapidly developing technology and an increasing number of products containing electrical or electronic functions, has led to discarded electrical and electronic equipment (EEE) being one of the fastest growing waste streams. The European Union (EU) has enacted several iterations of the Waste Electrical and Electronic Equipment (WEEE) Directive to address this complex waste stream. However, recycling dominates treatments for e-waste, despite the established 'waste hierarchy' showing waste prevention and reuse are generally preferable to recycling. This paper reports on 30 semi-structured interviews, undertaken across the EEE value chain, examining the impact of the WEEE Directive in the UK. The interviews confirmed that reuse takes place for a limited number of product types, mostly on a small scale. Additionally, whilst legislation has prompted innovation in recycling and higher capture rates, resource recovery is in practice limited to easily salvageable materials, whilst recovery of critical raw materials is often neglected. Furthermore, there is confusion around available collection networks, particularly for small WEEE, which consistently appears in residual waste streams. The waste hierarchy remains the key component of EU waste strategy and moving to the higher levels of the waste hierarchy is an essential part of achieving sustainable waste management and moving towards a circular economy. The paper proposes a series of measures to this end: promoting recovery routes and practices that facilitate reuse of suitable products, adapting recycling technology to increase recovery of critical raw materials and targeted policies to encourage the application of the waste hierarchy within a resource efficiency-oriented framework.